Stimulation of Cognitive Abilities of 5-6 Year Old Children through Ecoprint Activities - Indhira Syanna Amalia; Rista Sundari (Universitas Al-Hikmah Indonesia, 2025)
This study aims to explore the stimulation of cognitive abilities of children aged 5-6 years through ecoprint activities at Himawari Ngaliyan Semarang Kindergarten. The background of the study shows that children's cognitive development at an early age is crucial for long-term learning success. Ecoprint activities, which involve multisensory experiences with natural materials, are given optimal facts to stimulate children's cognitive abilities, especially the introduction of models, problem solving and classification. This research uses a qualitative method through a case study approach, which links documentation, questions and answers and observations. This lesson displays ecoprint activities are able to stimulate early childhood cognition. This activity provides a fun and meaningful learning experience, and encourages children to be more familiar with the surrounding environment. Thus, the integration of ecoprint activities in the early childhood education curriculum is highly recommended.